Structure–activity relationships and action mechanisms of collagen‐like antimicrobial peptides. Issue 1 (January 2017) - Masuda, Ryo; Dazai, Yui; Mima, Takehiko; Koide, Takaki
Abstract: An antimicrobial triple‐helical peptide, R3, was previously obtained from a collagen‐like combinatorial peptide library. In this research, based on structure–activity relationship studies ofR3, a more potent peptide, RR4, with increased positive net charge and charge density relative toR3, was developed.RR4 exhibited antimicrobial activity against both Gram‐negative and Gram‐positive bacterial strains, including multidrug‐resistant strains. Its action could be attributed to entry into cells and interactions with intercellular molecules such as DNA/RNA that inhibited cell division rather than increasing bacterial membrane permeability. Furthermore, RR4 exhibited remarkable stability in serum and low cytotoxicity.